Featured Answer

Asked on

how to evalute this function?

g(x) = x2 + 10x + 18

a) g (-5+√7)=

b) g(-2√3)=

Answers (3)

Collapse
jcallahan5cfd41f profile image
Collapse
cmun2kkeaa profile image

g(x) = x²+10x+18

a.) g[-5+√(7)] = [-5+√(7)]²+10[-5+√(7)]+18

g[-5+√(7)] = 32-10√(7)+10√(7)-50+18

g[-5+√(7)] = 0

Solution: g[-5+√(7)] = 0

b.) g[-2√(3)] = [-2√(3)]²+10[-2√(3)]+18

g[-2√(3)] = 12-20√(3)+18

g[-2√(3)] = 30-20√(3)

Solution: g[-2√(3)] = 30-20√(3)

Collapse
pevlcvplaa profile image

a)

g(-5 + √7) = (-5+√7)^2 + 10(-5+√7) + 18

(-5+√7)* (-5+√7) -50 + 10√7 + 18

25 - 5√7 - 5√7 + 7 - 32 + 10√7

-7 + 7 -10√7 + 10√7 = 0

Try the same steps for (b). Good luck.